Preparation of Mxene film electrode supported by high-flexibility aramid nanofiber substrate and application of Mxene film electrode in supercapacitor
By using high-flexible aramid nanofibers (ANF) as the substrate support layer, Mxene film electrodes with high mechanical flexibility and high conductivity were prepared, which solved the problem of limited application of Mxene electrodes in flexible supercapacitors, and achieved the effect of simplifying the preparation process and ensuring electrode performance.
Patent Information
- Application Number
- CN202411892713.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-25
AI Technical Summary
The application of Mxene electrodes in flexible supercapacitors is limited by mechanical flexibility and conductivity. The existing preparation methods are complex and prone to electrode damage and performance degradation.
Highly flexible aramid nanofibers (ANF) were used as the substrate support layer, and the Mxene thin film electrode pattern was prepared by vacuum filtration of ANF hydrosol and vacuum filtration of Mxene water dispersion on the filter membrane, combined with laser etching method, and finally peeling the filter membrane to obtain the Mxene thin film electrode supported by the ANF substrate.
The ANF/Mxene film electrode with high mechanical flexibility and high conductivity is achieved, the preparation process is simplified, the electrode transfer process is avoided, the structural integrity and performance stability of the electrode are ensured, and it is suitable for the preparation of flexible plane supercapacitors.
Smart Images

Figure CN119694798A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation of a highly flexible aramid nanofiber substrate-supported Mxene film electrode and the application of the same in a supercapacitor, belonging to the technical field of flexible energy storage devices. Background Art
[0002] In recent years, flexible, wearable, and portable electronic technologies have continued to develop and progress, showing great application potential in the fields of tracking fitness data, brain-computer interfaces, wearable medical devices, and smart home devices. The development and application of flexible wearable electronic devices urgently need energy storage and power supply devices that match them. Planar supercapacitors have the advantages of fast charging and discharging speed, long service life, miniaturization, and integrated preparation. As energy storage and power supply devices for flexible wearable electronic devices, they show good application prospects.
[0003] Electrodes are key components that determine the energy storage mechanism, energy storage characteristics, and mechanical flexibility of supercapacitors. As electrode materials for flexible supercapacitors, they need to have high conductivity and high mechanical flexibility. The two-dimensional material Ti3C2Tx (MXene) has the characteristics of high conductivity, large specific surface area, high theoretical specific capacitance, and adjustable physical and chemical properties. It is a new type of supercapacitor electrode material with good application prospects. However, the self-supporting MXene electrode has poor mechanical flexibility, and the operability of miniaturized and integrated planar electrodes is not strong, which limits its application in flexible supercapacitors. Adding ingredients such as cellulose nanofibers to MXene can improve the mechanical properties of MXene films, but due to the electrical insulation characteristics of cellulose nanofibers, the conductivity of the electrode and the storage capacity of the supercapacitor are reduced (Adv. Mater. 2019, 31, 1902977). The template-assisted vacuum filtration method is used to first prepare the Mxene electrode on the filter membrane, and then transfer the electrode to a transparent flexible substrate such as polyethylene terephthalate. This is currently a common method for preparing Mxene flexible electrodes and supercapacitors (J. Mater. Chem. A, 2019, 7, 9478). However, substrate transfer complicates the preparation process and may cause problems such as electrode damage, short circuit, and device performance degradation, which is not conducive to the large-scale preparation of Mxene flexible electrodes. Summary of the invention
[0004] In order to solve the above problems and shortcomings of Mxene electrodes and supercapacitors, the present invention provides a preparation of Mxene thin film electrodes supported by a highly flexible aramid nanofiber (ANF) substrate and its application in supercapacitors. The ANF-supported Mxene thin film electrode, represented by ANF / Mxene thin film electrode, is composed of an ANF substrate and a Mxene conductive film, wherein the thickness of the ANF substrate layer is 2-20 microns, and the thickness of the Mxene conductive film is 1-100 microns; the preparation method of the ANF / Mxene thin film electrode refers to successively performing vacuum filtration of ANF aqueous sol and vacuum filtration of Mxene aqueous dispersion on a filter membrane, using a laser etching method to prepare a Mxene electrode pattern, and finally peeling off the bottom filter membrane to obtain an ANF membrane-supported Mxene planar electrode. The preparation method is simple to operate, low in cost, high in efficiency, easy to miniaturize and integrate, and does not require an electrode transfer process, can ensure the structural integrity and performance stability of the Mxene electrode, and the prepared ANF / Mxene electrode has high mechanical flexibility and high conductivity, and is successfully used to prepare flexible planar supercapacitors.
[0005] The object of the present invention can be achieved by the following technical solutions:
[0006] The first object of the present invention is to provide a highly flexible ANF / Mxene thin film electrode structure, which is composed of an ANF ultra-thin transparent substrate support layer and a Mxene conductive film layer, wherein the ANF support layer has a thickness of 2-20 microns and the Mxene conductive film layer has a thickness of 1-100 microns;
[0007] The second object of the present invention is to provide a method for preparing a highly flexible ANF / Mxene thin film electrode, the preparation method comprising the following steps:
[0008] 1. Preparation of ANF hydrosol: Add commercial Kevlar fiber into a DMSO-H2O mixed solvent containing excess KOH, and stir magnetically until the fiber is completely dissolved to obtain a dark red and clear ANF dispersion; take an appropriate amount of ANF dispersion, further add deionized water, and stir magnetically to obtain ANF hydrosol;
[0009] 2. Preparation of MXene aqueous dispersion:
[0010] Adding Mxene to a proper amount of water, dispersing Mxene by ultrasound, hand shaking or magnetic stirring, etc., to obtain a Mxene aqueous dispersion;
[0011] 3. Preparation of ANF hydrogel support layer: Measure a certain volume of ANF colloid and perform vacuum filtration on a filter membrane to obtain an ANF hydrogel layer;
[0012] 4. Preparation of Mxene film: The Mxene aqueous dispersion is further vacuum filtered on the ANF hydrogel layer to obtain a three-layer composite precursor film of filter membrane / ANF / Mxene;
[0013] 5. ANF / Mxene thin film electrode pattern laser etching preparation: The Mxene planar electrode pattern was prepared by laser etching method, dried, and finally the bottom filter membrane was peeled off to obtain the ANF / Mxene planar electrode.
[0014] The present invention further comprises the following steps:
[0015] 1a Prepare DMSO-H2O mixed solvent: the volume ratio of deionized water in the mixed solvent is 1%-10%, and magnetic stirring is performed for 5-60 minutes;
[0016] 1b Add KOH to the DMSO-H2O mixed solvent and stir magnetically for 10-50 minutes to obtain a KOH supersaturated DMSO-H2O solution;
[0017] 1c In the KOH supersaturated DMSO-H2O solution, according to the required ANF solution concentration, add an appropriate amount of commercial Kevlar fiber, continue magnetic stirring until the fiber is completely dissolved, and obtain a dark red ANF dispersion. The concentration of the ANF dispersion is 0.5-10 mg / ml.
[0018] The present invention further comprises the following steps:
[0019] According to the prepared ANF colloid concentration, take an appropriate amount of ANF dispersion, add 2-5 times the volume ratio of deionized water, and stir magnetically until a uniform ANF colloid is obtained with a colloid concentration of 0.1-10 mg / ml;
[0020] The present invention further comprises the following steps:
[0021] Using Ti3AlC2 as raw material, removing aluminum from the raw material by in-situ HCl-LiF or HF etching, washing the obtained product by hydrochloric acid and deionized water centrifugation for multiple times to obtain a Mxene precursor; adding deionized water, exfoliating by ultrasound, turbine vibration or hand shaking to obtain a Mxene aqueous dispersion, the dispersion concentration of which is 0.5-10 mg / ml;
[0022] Furthermore, in the step 3, the filter membrane used in the vacuum filtration in the preparation process of the ANF hydrogel support layer includes but is not limited to polytetrafluoroethylene (PTFE) filter membrane, nylon filter membrane, Celgard 3501 filter membrane, etc.;
[0023] The present invention further comprises that the laser etching preparation conditions of the ANF / Mxene thin film electrode pattern in step 5 are as follows: the laser power is 0.2-5W, and the laser scanning rate is 500-5000mm / s:
[0024] The present invention further comprises that in step 5, the ANF / Mxene thin film electrode pattern is prepared by laser etching, and the drying conditions are drying in a vacuum furnace at 30-100 degrees for 30-180 minutes.
[0025] Furthermore, in the ANF / Mxene double-layer film of the present invention, the thickness of the ANF support layer is 2-20 microns, and the thickness of the Mxene electrode film is 1-100 microns.
[0026] The ANF / Mxene thin film electrode is used to construct a planar supercapacitor.
[0027] Compared with the prior art, the present invention has the following effects and benefits:
[0028] 1. The ANF / Mxene thin film electrode is composed of an ANF ultra-thin substrate and a Mxene conductive film. The ANF substrate layer has high mechanical flexibility and ultra-thin thickness (only 2-20 μm), which can provide support for the Mxene electrode and enhance the mechanical flexibility of the Mxene electrode without reducing the conductivity of the Mxene electrode, thus meeting the needs of flexible supercapacitors.
[0029] 2. The preparation method of the ANF / Mxene thin film electrode of the present invention refers to vacuum filtration of ANF aqueous dispersion and vacuum filtration of Mxene aqueous dispersion on the filter membrane, and then preparing the Mxene electrode pattern by laser etching, and finally peeling off the bottom filter membrane to obtain the Mxene planar electrode supported by the ANF substrate. The preparation method does not require an electrode transfer process, can ensure the structural integrity and stable performance of the Mxene electrode, and has a simple preparation process, low cost, high efficiency, and is easy to prepare the miniaturized and integrated electrode. The ANF / Mxene thin film electrode prepared by the present invention and the sulfuric acid-polyvinyl alcohol hydrogel electrolyte are used to construct a solid-state planar supercapacitor, and the charge and discharge test is carried out. The supercapacitor shows good power storage characteristics and extremely high anti-deformation ability, and does not reduce the conductive performance of the Mxene electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a photo of the ANF / Mxene planar interdigitated electrode prepared in an embodiment of the present invention.
[0031] Figure 2 Photos of ANF / Mxene series and parallel integrated planar interdigitated electrodes prepared in an embodiment of the present invention.
[0032] Figure 3 These are photos of supercapacitors constructed using the ANF / Mxene planar interdigitated electrodes prepared in an embodiment of the present invention in flat and folded states.
[0033] Figure 4 Cyclic voltammograms of the supercapacitor constructed using the ANF / Mxene planar interdigitated electrodes prepared in the embodiment of the present invention in the initial flat state, and after 5000 and 10000 flat-folded cycles.
[0034] Figure 5 The capacitance retention rate of the supercapacitor constructed using the ANF / Mxene planar interdigitated electrodes prepared in accordance with the present invention varies with the number of flattening-folding cycles. The figure indicates that the capacitance retention rate after 10,000 folding cycles is 90%.
[0035] Figure 6 These are photos of supercapacitors constructed using PTFE / Mxene planar interdigitated electrodes prepared in the comparative example of the present invention in the flat and folded states.
[0036] Figure 7 Cyclic voltammograms of a supercapacitor constructed using the PTFE / Mxene planar interdigitated electrodes prepared as a comparative example of the present invention in the initial flat state, and after 500 and 2500 flat-folded cycles.
[0037] Figure 8 The capacitance retention rate of the supercapacitor constructed using the PTFE / Mxene planar interdigitated electrode prepared as a comparative example of the present invention varies with the number of flattening-folding cycles. The figure indicates that the capacitance retention rate after 2500 folding cycles is 30%. DETAILED DESCRIPTION
[0038] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some variations and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0039] Any features such as preparation methods, materials, structures or composition ratios that are not clearly described in this technical solution shall be deemed as common technical features disclosed in the prior art.
[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0041] Example
[0042] This embodiment provides a method for preparing a Mxene thin film electrode supported by a highly flexible ANF substrate, and the specific steps are as follows:
[0043] 1. Preparation of ANF colloid: Mix 100 ml DMSO with 4 ml deionized water, add 0.3 g KOH and stir magnetically for 10 min, then add 0.208 g commercial Kevlar fiber, stir magnetically for 2 h until the fiber dissolves, and obtain a dark red ANF dispersion with a concentration of 2 mg / ml; take 20 ml of 2 mg / ml ANF dispersion, add 60 ml deionized water, stir magnetically for 1 h, and obtain an ANF colloid with a concentration of 0.5 mg / ml;
[0044] 2. Preparation of Mxene aqueous dispersion: Mxene dispersion was prepared using Ti3AlC2 as raw material by HCl-LiF in-situ etching method: 1g LiF was added to 20ml 9M hydrochloric acid solution, stirred at room temperature for 10min, and then 1g Ti3AlC2 powder was slowly added, stirred and reacted at 45 degrees for 48h, and the aluminum layer in Ti3AlC2 was selectively etched away; the obtained product was washed by centrifugation with hydrochloric acid and deionized water for multiple times to obtain Mxene precursor; deionized water was added to the Mxene precursor, and exfoliation and dispersion were performed by ice bath ultrasonic method to obtain Mxene aqueous dispersion with a concentration of 2mg / ml;
[0045] 3. Preparation of ANF hydrogel support layer: Take 30 ml of 0.5 mg / ml ANF colloid and use a PTFE filter membrane with a pore size of 0.45 μm and a diameter of 4 cm for vacuum filtration to obtain a hydrogel-like ANF support layer;
[0046] 4. Preparation of Mxene film: 12.56 ml of Mxene aqueous dispersion with a concentration of 2 mg / ml was taken and vacuum filtered on the ANF hydrogel layer to obtain a PTFE filter membrane / ANF / Mxene three-layer composite precursor membrane; 5. Laser etching preparation of ANF / Mxene film electrode pattern: The PTFE filter membrane / ANF / Mxene three-layer composite precursor membrane was dried in a vacuum oven at 50 degrees for 60 minutes, and then the electrode pattern was designed using AutoCAD software. Under the control of a computer program, laser etching was performed with a laser wavelength of 1064 nm. Under the conditions of a laser power of 0.4 W and a scanning rate of 2000 mm / s, a Mxene planar interdigitated electrode pattern was prepared. Finally, the bottom filter membrane was peeled off to obtain an ANF / Mxene planar interdigitated electrode.
[0047] In the ANF / Mxene thin film electrode prepared in the embodiment, the surface density of the Mxene film is 2 mg / cm 2 ,The thickness of the ANF substrate layer is 5μm, and the conductivity of the Mxene film is ~6000S / cm. Figure 1 This is a photo of a single ANF / Mxene planar interdigitated electrode prepared in Example 1. The light yellow substrate is the ANF support layer, and the ruler is used to mark the electrode structure. The preparation method of the present invention can be used to conveniently and quickly prepare miniaturized, series-parallel integrated ANF / Mxene planar electrodes. Figure 2 The ANF / Mxene planar miniaturized series-parallel electrode prepared in the example has an area of 12.56 cm 2 32 Mxene interdigital electrodes were prepared on the ANF substrate, and the electrodes were straight and structurally complete.
[0048] In order to prove that the ANF / Mxene electrode prepared by the implementation method of the present invention can be applied to a flexible supercapacitor, the ANF / Mxene planar electrode prepared in the embodiment is coated with a polyvinyl alcohol-sulfuric acid hydrogel electrolyte and dried at room temperature for 24 hours to form a Figure 3 The solid-state planar supercapacitor shown has a device length of 3 cm. The supercapacitor is subjected to a flattening-folding-flattening operation, with flattening-folding-flattening being one cycle, and the charge-discharge cyclic voltammetry (CV) curves at different cycle numbers are tested. Figure 4 The CV curves are the initial flat state, the 5000th folding cycle, and the 10000th folding cycle. It can be seen that the three curves are almost overlapping, indicating that after 10,000 foldings, the energy storage characteristics of the supercapacitor change very little and the device has good mechanical flexibility. Based on the CV curves, the capacitance retention rate (C n %), calculated as C n %=C n / C0 *100%, where C0 is the capacitance value of the supercapacitor in the initial flat state. After folding cycles, the higher the capacitance retention rate, the better the flexibility of the capacitor. Figure 5 It is the capacitance retention rate of the supercapacitor under different folding cycles. After 10,000 folding cycles, the capacitance retention rate is still as high as 90%, which proves the feasibility of using the ANF / Mxene electrode prepared by the implementation method of the present invention to construct a flexible supercapacitor, which can meet the needs of flexible wearable electronic devices.
[0049] Comparative Example
[0050] The basic content of this comparative example is the same as that of the embodiment, except that: the Mxene aqueous dispersion is directly vacuum filtered on the PTFE filter membrane to obtain a PTFE filter membrane-supported Mxene electrode, which is represented by PTFE / Mxene. Figure 6This is a PTFE / Mxene planar interdigitated electrode prepared in a comparative example, and the white substrate is a PTFE filter membrane. As in the example, a solid-state supercapacitor was constructed based on a PTFE / Mxene planar interdigitated electrode and a polyvinyl alcohol-sulfuric acid hydrogel electrolyte, and a flat-folded-flat cycle operation was performed, and a CV curve was tested at the same time. Figure 7 These are the CV curves of the initial flat state, the 500th folding cycle, and the 2500th folding cycle. It can be seen that as the number of foldings increases, the area of the CV curve decreases significantly, indicating that folding causes the energy storage characteristics of the device to deteriorate. Figure 7 is the capacitance retention rate under different folding cycles. After only 2500 foldings, the capacitance value of the supercapacitor is reduced to 30% of the initial state, proving that the mechanical flexibility of the Mxene electrode supported by the PTFE filter prepared in the comparative example is very poor. This further illustrates the feasibility of the ANF / Mxene electrode prepared by the implementation method of the present invention for constructing a supercapacitor with high mechanical flexibility, which can meet the needs of flexible wearable electronic devices.
Claims
1. A method for preparing a highly flexible ANF / Mxene thin film electrode, characterized in that: The ANF / Mxene thin film electrode is composed of an ANF ultra-thin transparent substrate support layer and a Mxene conductive film layer, wherein the ANF support layer has a thickness of 2-20 microns and the Mxene conductive film layer has a thickness of 1-100 microns; The preparation method comprises the following steps: S1. Preparation of ANF hydrosol: commercial Kevlar fiber was added into KOH supersaturated DMSO-H2O solution and magnetically stirred until the fiber was completely dissolved to obtain a dark red and clear ANF dispersion; deionized water was further added into the ANF dispersion and magnetically stirred to obtain ANF hydrosol; The concentration of the ANF dispersion is 0.5-10 mg / ml; the concentration of the colloid is 0.1-10 mg / ml; S2. Preparation of Mxene aqueous dispersion: adding Mxene to water, dispersing Mxene by stirring, and obtaining Mxene aqueous dispersion; The concentration of the Mxene aqueous dispersion is 0.5-10 mg / ml; S3. Preparation of ANF hydrogel support layer: ANF colloid was measured and vacuum filtered on a filter membrane to obtain an ANF hydrogel layer; S4. Preparation of Mxene film: The Mxene aqueous dispersion is further vacuum filtered on the ANF hydrogel layer to obtain a filter membrane / ANF / Mxene three-layer composite precursor film; S5. Preparation of ANF / Mxene thin film electrode pattern by laser etching: After the filter membrane / ANF / Mxene three-layer composite precursor film is dried, a Mxene planar electrode pattern is prepared on the basis of the filter membrane / ANF / Mxene three-layer composite film by laser etching. Finally, the bottom filter membrane is peeled off to obtain the ANF / Mxene planar electrode.
2. The method for preparing a highly flexible ANF / Mxene thin film electrode according to claim 1, characterized in that: Preparation of KOH supersaturated DMSO-H2O solution in step S1: a. In the DMSO-H2O mixed solvent, the volume ratio of deionized water is 1%-10%, and magnetic stirring is performed for 5-60 minutes; b. Add KOH to the DMSO-H2O mixed solvent and stir magnetically for 10-50 minutes to obtain a KOH-supersaturated DMSO-H2O solution.
3. The method for preparing a highly flexible ANF / Mxene thin film electrode according to claim 1, characterized in that: The preparation of the Mxene aqueous dispersion in step S2 is as follows: Using Ti3AlC2 as raw material, the aluminum element in the raw material is removed by in-situ HCl-LiF or HF etching method, and the obtained product is centrifuged and washed with hydrochloric acid and deionized water to obtain a Mxene precursor; deionized water is added, and the product is stripped by ultrasound, turbine vibration or hand shaking to obtain a Mxene aqueous dispersion.
4. The method for preparing a highly flexible ANF / Mxene thin film electrode according to claim 1, characterized in that: The filter membrane in step S3 is a polytetrafluoroethylene filter membrane, a nylon filter membrane, or a Celgard 3501 filter membrane.
5. The method for preparing a highly flexible ANF / Mxene thin film electrode according to claim 1, characterized in that: The laser etching preparation conditions of the ANF / Mxene thin film electrode pattern in step S5 are a power of 0.2-3 W and a laser scanning rate of 500-5000 mm / s.
6. The method for preparing a highly flexible ANF / Mxene thin film electrode according to claim 1, characterized in that: In step S5, the drying condition is drying in a vacuum oven at 30-100 degrees for 30-180 minutes.
7. A highly flexible ANF / Mxene thin film electrode, characterized in that: The method is prepared by any one of claims 1 to 6.
8. The highly flexible ANF / Mxene thin film electrode according to claim 7, characterized in that: The ANF / Mxene thin film electrode is double-layered, the thickness of the lower ANF support layer is 2-20 microns, and the thickness of the upper Mxene electrode film is 1-100 microns.
9. The use of a highly flexible ANF / Mxene thin film electrode according to claim 7, characterized in that: The ANF / Mxene thin film electrode is used to construct a planar supercapacitor.
10. The use of a highly flexible ANF / Mxene thin film electrode according to claim 8, characterized in that: The ANF / Mxene thin film electrode is used to construct a planar supercapacitor.